Avaliação do Ciclo de Vida e Serviços Ecossistêmicos: um estudo de caso aplicado a diferentes sistemas de produção de leite - Silva, Daiane Vitória da (2022)
Milk production stands out in the world economy. In the last twenty years, its production has increased by 340 million tons. However, there is a concern about the environmental impacts of cattle raising activities. For example, milk production is considered one of the main sources of greenhouse and gas emissions, in addition to that other impacts can be harmed for the environment. Thus, sustainability assessment tools are essential to contribute to sustainability on dairy farms. On top of that, Life Cycle Assessment (LCA) is considered the main technique used for determining the environmental profile of products. However, there are still gaps concerning the assessment of product’s impacts from the perspective of Ecosystem Services (ES), especially when the production activity demands the use of natural resources, this has being an aspect that can interfere in the provision of ES. The aim of this study is to determine the Net Environmental Performance (NEP) of different dairy production systems. Consequently a case study was conducted in a farm characterized as confined compost barn, located in the southwest of the state of São Paulo, using 1 kg of raw milk with average fat (3.75%) and protein (2.97%) correction as the functional unit. A framework was applied to calculate the NEP by combining LCA with SE, where the ecosystem impacts and benefits were converted into monetary units. To interpret of the results, a scenario was performed to compare the system studied together with confined and semi-confined milk production systems in the regions of Paraná and Minas Gerais. The NEP was calculated only for a gate-to-gate system view, presenting an average value of R$ -0.05 BRL/kg FPCM milk, for the case study system. The other milk production scenarios in Brazil also presented negative NEP, meaning that the environmental impacts were greater than the benefits generated on each system. Finally, it is feared that the steps developed in this study for the calculation of the DAL can be used in further case studies considering also an ecological, SE-oriented view and from a more completed perspective in the product life cycle view, i.e. cradle-to-grave.